Determinants of E-wallet User Satisfaction: Digital Financial Literacy, Ease of Use, and Trust in Generation Z - A. Aisyah; Hadi Ismanto (Golden Ratio of Mapping Idea and Literature Format, 2026)
The rapid development of financial technology has driven significant transformations in digital payment systems, particularly through e-wallets. Generation Z, as digital natives and active e-wallet users, faces challenges related to digital financial literacy that could potentially impact their satisfaction levels. The purpose of this study is to analyze the factors influencing e-wallet user satisfaction among Generation Z, with a focus on the role of digital financial literacy, ease of use, and trust as key determinants, thus providing guidance for digital financial service providers in designing strategies to improve user satisfaction. This study uses a quantitative approach with primary data obtained through a questionnaire in the form of Google Forms. The population of this study is Generation Z in Jepara Regency who use e-wallets. The sampling technique used is non-probability sampling with a purposive sampling method. The criteria used by researchers to select the sample in this study are Generation Z born between 1997 and 2012, domiciled in Jepara, and have experience in using e-wallets (e.g., Dana, GoPay, OVO, ShopeePay, LinkAja). Data analysis was conducted using SmartPLS through outer model testing, inner model testing, and hypothesis testing. The research results show that digital financial literacy, ease of use, and trust have a positive and significant impact on user satisfaction. Thus, a good understanding of digital financial products, ease of use, and trust are key factors in determining user satisfaction. Operating an e-wallet and trusting the security of the service are the main keys to increasing Generation Z user satisfaction with e-wallets amidst increasingly fierce competition in the digital economic ecosystem.